2020
DOI: 10.1364/oe.397119
|View full text |Cite
|
Sign up to set email alerts
|

Designing the phase and amplitude of scalar optical fields in three dimensions

Abstract: The ability to generate any arbitrarily chosen optical field in a three-dimensional (3D) space, in the absence of any sources, without modifying the index of refraction, remains an elusive but much-desired capability with applications in various fields such as optical micromanipulation, imaging, and data communications, to name a few. In this work, we show analytically that it is possible to generate any desired scalar optical field with predefined amplitude and phase in 3D space, where the generated field is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…One might argue that these limitations can be bypassed by specifying the way the nearby fields are distributed so that the intensity goes to zero at the desired singularity locations. By doing so, one can then construct the closest wave-equation solution to the predefined phase and amplitude distribution using analytic techniques 23 . However, in specifying one spatial pattern adjacent to the singularity, one will reduce the space of acceptable designs by excluding other optical fields that also contain the desired singularity structure, potentially excluding better-behaved fields which more closely approximate the desired field distribution.…”
Section: Resultsmentioning
confidence: 99%
“…One might argue that these limitations can be bypassed by specifying the way the nearby fields are distributed so that the intensity goes to zero at the desired singularity locations. By doing so, one can then construct the closest wave-equation solution to the predefined phase and amplitude distribution using analytic techniques 23 . However, in specifying one spatial pattern adjacent to the singularity, one will reduce the space of acceptable designs by excluding other optical fields that also contain the desired singularity structure, potentially excluding better-behaved fields which more closely approximate the desired field distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Figures 6(a) and (b) exhibit two examples of structured light following arbitrary trajectories in 3D. Beams of this nature can either be inverse designed by backpropagating the target pattern to an initial plane that defines the desired hologram [35] or by sculpting the incident waveform into an ensemble of co-propagating modes with different longitudinal wavevectors which beat along the direction of propagation, thereby modulating the resulting envelope at-will via multimode light interference. Frozen Waves and optical tractor/conveyor beams are two key examples of the latter approach; both of which have [35].…”
Section: Statusmentioning
confidence: 99%
“…The concept of frozen waves was introduced in 2004 [11], where it was shown that one can generate stationary localized wave fields with a longitudinal intensity pattern that can assume any desired shape. Subsequently, more complex 3D control of optical fields was demonstrated [12,13]. The interference pattern of two coherent beams can generate a simple sinusoidal periodic pattern that can achieve the required quasi phase matching in a way similar to that of periodic poling.…”
Section: Introductionmentioning
confidence: 99%